Development, characterization, and assessment of PLAROsomal vesicular system of curcumin for enhanced stability and therapeutic efficacy - Somnath Devidas Bhinge; Sheetal Kamble; Dheeraj Randive; Mangesh Bhutkar; Sameer Nadaf; Abhijit Merekar; Kailas Sonawane; Namdeo Jadhav; Asiya Makandar; Mohd Shahnawaz Khan; Shailendra Gurav (Future Journal of Pharmaceutical Sciences, 2024)
Abstract Background Curcumin (CUR) is a natural polyphenol and one of the key phytoconstituents found in the rhizomes of Curcuma Longa. It exhibits various pharmacological properties, encompassing antioxidant, anticancer effects, antiseptic, and anti-inflammatory, among several others. A significant drawback of using CUR is its limited bioavailability, which primarily depends on gut microorganisms responsible for converting it into its bioavailable form. Therefore, the contemporary study intended to formulate a novel PLAROsomal vesicular delivery of CUR, i.e., CUR-PLAROsomes employing a design of experiments approach to examine the influence of various process parameters, such as particle size and drug percentage release. Result The prepared CUR-PLAROsomes were characterized for their physicochemical properties using various hyphenated tools. The CUR-PLAROsomes exhibited sizes ranging from 40 to 300 nm, and the optimized batch demonstrated a drug entrapment of 86.38 ± 0.22%. In-vitro anticancer studies were conducted using human colorectal adenocarcinoma cells (COLO320DM) and human breast adenocarcinoma (MCF-7). CUR-PLAROsomes exhibited significant in-vivo anti-inflammatory potential against carrageenan-induced paw edema. CUR-PLAROsomes were more potent against COLO320DM and MCF-7 cell lines, even at lower concentrations, than pure CUR. Conclusion Furthermore, based on the observations, it exhibits potential as an anti-inflammatory agent, suggesting that PLAROsomes are an effective vesicular drug delivery system. Highlights Newly introduced PLARosome is a next generation of Liposomes which have gain popularity owing to its better adaptability to overcome leakage problem of vesicular drug delivery system. This is the pioneer attempt to prepare Curcumin-loaded PLARosome as an anti-cancer and anti-inflammatory activity. Nano size of the PLAROsomes may contribute to enhance the efficacy of Curcumin as a target specific drug delivery system. Site specific delivery of phytoconstituents is possible by use of PLAROsomes as a novel drug delivery system. Graphical abstract